2020
DOI: 10.1542/peds.2019-3365
|View full text |Cite
|
Sign up to set email alerts
|

Early Postnatal Discharge for Infants: A Meta-analysis

Abstract: OBJECTIVES:To describe the proportion of children screened by the Modified Checklist for Autism in Toddlers (M-CHAT), identify characteristics associated with screen completion, and examine associations between autism spectrum disorder (ASD) screening and later ASD diagnosis. METHODS:We examined data from children attending 18-and 24-month visits between 2013 and 2016 from 20 clinics within a health care system for evidence of screening with the M-CHAT and subsequent coding of ASD diagnosis at age .4.75 years.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 39 publications
0
19
0
2
Order By: Relevance
“…Previous research, including systematic reviews, have reported varied results with respect to early discharge and infant rehospitalization. 10,[34][35][36] A recent meta-analysis, which included RCTs and quasi-experimental studies, and Cochrane review, both report an association between early hospital discharge (<48 hours for vaginal and <96 hours for cesarean) and infant readmission within 28 days. 10,36 However, findings from both studies are driven (87.6% and 74% weight, respectively) by a single center Egyptian RCT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research, including systematic reviews, have reported varied results with respect to early discharge and infant rehospitalization. 10,[34][35][36] A recent meta-analysis, which included RCTs and quasi-experimental studies, and Cochrane review, both report an association between early hospital discharge (<48 hours for vaginal and <96 hours for cesarean) and infant readmission within 28 days. 10,36 However, findings from both studies are driven (87.6% and 74% weight, respectively) by a single center Egyptian RCT.…”
Section: Discussionmentioning
confidence: 99%
“…10,[34][35][36] A recent meta-analysis, which included RCTs and quasi-experimental studies, and Cochrane review, both report an association between early hospital discharge (<48 hours for vaginal and <96 hours for cesarean) and infant readmission within 28 days. 10,36 However, findings from both studies are driven (87.6% and 74% weight, respectively) by a single center Egyptian RCT. 37 In general, findings from RCTs are limited by the application of highly restrictive criteria for early discharge, inadequate sample sizes to detect clinical effects, and variation in post-discharge services.…”
Section: Discussionmentioning
confidence: 99%
“…During the COVID-19 era, data from U.S. healthcare systems discussed above showed that early discharge has not been shown to increase readmissions; in fact, a decrease in readmissions has been observed [22,23]. The reason for this is unclear, and contradicts the findings of a pre-pandemic meta-analysis which found infants discharged early were more likely to be readmitted within 28 days [2]. In the meta-analysis, early was defined as less than 48 h for vaginal and 96 h for cesarean delivery, which exceeds the average postnatal LOS in several developed countries [2,18].…”
Section: Discussionmentioning
confidence: 95%
“…The authors concluded that early discharge probably leads to a higher risk of infant readmission within 28 days of birth [17]. A 2020 meta-analysis by Jones et al pooled readmission data from seven randomized controlled studies and found that infants discharged early were more likely to be readmitted within 28 days compared to standard discharge [2].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation